Slow Dancing: Mind, Body, and Sexuality in a New Relational Psychoanalysis. Issue 2 (3rd May 2016) - Slavin, Jonathan H.; Rahmani, Miki
Abstract : Recent psychoanalytic writing has involved an effort to reintegrate the body and bodily experiencing into our understanding of the construction of the mind. This integration is critical for psychoanalysis because, as is increasingly clear in science, the physical brain, the body's experiencing organ, and mind are one. As Kandel (2013) noted, "Psychotherapy is a biological treatment, a brain therapy. It produces lasting, detectable physical changes in our brain" (para. 11). Yet can we return to the brain, to the body, to materiality, to trying to find our minds in the body without returning to a fundamental psychoanalytic integration of the absolute centrality of sexuality in our mental development? Mustn't a new relational psychoanalysis that reckons with the body in the mind also reckon with Freud's compelling understanding of our sexual experiencing at the core and edge of our relational worlds? In this paper we explore some of the ways one's individual sexuality, one's sexual fingerprint, embodies all of the potential for human experiencing in ourselves and in relationship: the driven and surrendering, the edges of passion and violation, the paradox of relationship and dissociation, attunement and personal desire. Our focus is on sexuality in the powerful, brain-changing interactions between patients and therapists in the treatment process.